Respiratory Commensal Bacteria Corynebacterium pseudodiphtheriticum Improves Resistance of Infant Mice to Respiratory Syncytial Virus and Streptococcus pneumoniae Superinfection - Kanmani, Paulraj; Clua, Patricia; Vizoso-Pinto, Maria G.; Rodriguez, Cecilia; Alvarez, Susana; Melnikov, Vyacheslav; Takahashi, Hideki; Kitazawa, Haruki; Villena, Julio (Frontiers in microbiology, 2017)
is a Gram-positive bacterium found as a member of the normal microbiota of the upper respiratory tract. It was suggested that may be potentially used as a next-generation probiotic for nasal application, although no deep studies were performed in this regard. We hypothesized that human isolate strain 090104 is able to modulate the respiratory innate immune response and beneficially influence the resistance to viral and bacterial infections. Therefore, in the present study we investigated how the exposure of infant mice to nasal priming with viable or non-viable 090104 influences the respiratory innate immune response triggered by Toll-like receptor (TLR)-3 activation, the susceptibility to primary Respiratory Synsytial Virus (RSV) infection, and the resistance to secondary pneumonia. We demonstrated that the nasal priming with viable 090104 differentially modulated TLR3-mediated innate antiviral immune response in the respiratory tract of infant mice, improving their resistance to primary RSV infection, and secondary pneumococcal pneumonia. In association with the protection against RSV-pneumococcal superinfection, we found that viable improved lung CD3 CD4 IFN-γ , and CD3 CD4 IL-10 T cells as well as CD11c SiglecF IFN-β alveolar macrophages. Of interest, non-viable bacteria did not have the same protective effect, suggesting that colonization is needed for achieving its protective effect. In conclusion, we present evidence that nasal application of viable could be thought as an alternative to boost defenses against RSV and secondary pneumococcal pneumonia, which should be further studied and validated in clinical trials. Due to the absence of a long-lasting immunity, re-infection with RSV throughout life is common. Thus, a possible perspective use could be a seasonal application of a nasal probiotic spray to boost respiratory innate immunity in immunocompetent subjects.